2011
DOI: 10.1525/jer.2011.6.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Community-Based Processes for Research Ethics Review and Institution-Based IRBs: A National Study

Abstract: Community groups are implementing research ethics review processes to determine whether and how research is conducted in their communities. We report on a survey of 109 of these community-based review processes about their relationships with institution based research ethics boards (I-REBs). Ninety-two percent reported that studies they review were also reviewed by an I-REB. Over half characterized their relationship with I-REBs positively. Those with positive relationships were significantly more likely to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 15 publications
(20 reference statements)
0
30
0
Order By: Relevance
“…16,49,5861 Authors suggest that IRBs (1) are concerned with individuals and not with community well-being 16,49,61 ; (2) require that all research procedures be approved before research has begun, even though CBPR is dynamic and often requires continual assessment and ongoing adjustments to research protocols 58,59 and (3) are unfamiliar with CBPR, which may use nontraditional research procedures and hold different beliefs about features IRBs prioritize in their evaluations (e.g., assumptions about data ownership). 50,59,60 …”
Section: Resultsmentioning
confidence: 99%
“…16,49,5861 Authors suggest that IRBs (1) are concerned with individuals and not with community well-being 16,49,61 ; (2) require that all research procedures be approved before research has begun, even though CBPR is dynamic and often requires continual assessment and ongoing adjustments to research protocols 58,59 and (3) are unfamiliar with CBPR, which may use nontraditional research procedures and hold different beliefs about features IRBs prioritize in their evaluations (e.g., assumptions about data ownership). 50,59,60 …”
Section: Resultsmentioning
confidence: 99%
“…Given that it is an open question whether community psychology needs its own statement of ethical principles, it seemed useful to go back to the beginning, so to speak, and explore our views of the fundamental ethical concepts outlined in the Belmont Report. In choosing to ground our analysis in the Belmont Report, we also acknowledge and engage critiques of this report, particularly those from the multidisciplinary literature on community‐based participatory research (CBPR) (Flicker, Travers, Guta, McDonald, & Meagher, ; Mikesall, Bromley, & Khodyakov, ; Ross et al., ; Shore, ; Shore, Drew, Brazauskas, & Seifer, ; Weijer & Emanuel, ). CBPR scholars have observed that as a document originally intended primarily for medical and laboratory‐based studies, the Belmont Report was not written with community‐based research in mind, and thus, it is necessary to expand our thinking to consider what these core Principles could mean in field‐based, social action research.…”
Section: Introductionmentioning
confidence: 99%
“…There is also growing attention to IRB review of CEnR (Flicker et al, 2007; Malone et al, 2006; Shore, 2007; Shore et al, 2011; Silverstein et al, 2008). …”
mentioning
confidence: 99%